E-commerce consumer purchasing decisions in Sonora - Bocanegra Gastelum, Carmen Otilia (Posgrados de la División de Ciencias Económica Administrativas, 2023)
Given the importance that the online consumer represents for the expansión of electronic commerce in Sonora, the article presents as an objective, to to investigate in the Sonora entity, the profile of the final consumer who buys through electronic retail commerce, since it expresses choices and decisions that it is important to know for the generation of strategies by local retailers. To achieve the objective, a simple random sample of 400 online surveys applied to Internet users over 18 years of age, who have made at least one purchase through electronic commerce, was used. Among the most outstanding results are the following: consumers between 18 and 25 years old (65%) are the ones who buy the most through e-commerce; 63.75% of the total are students; the amount of income of the most consuming population ranges between $6,000 and $12,000 pesos per month by 68%; 56% decide to buy to find a lower price; 70.6% still mistrust e-commerce; This is mainly based on the insecurity in payment with bank cards with 58%; The platform most used by Internet users, both for local and international consumption, is Amazon, with 76% and 86%, respectively; The most demanded market is the United States with 84%, among other indicators that define the profile of the digital consumer in Sonora.